QoS Evaluation of Cellular Wireless Networks with Non-Classical Traffic and Queuing Handoff Requests - Samanta, Rajkumar; Bhattacharjee, Partha; Sanyal, Gautam (INFOCOMP Journal of Computer Science, 2010)
In this paper, a model is proposed for the QoS evaluation of cellular wireless networks by queuing handoff requests instead of reserving guard channels. Usually, prioritized handling of handoff calls is done with the help of guard channel reservation. Using the proposed model, the performance of the networks is estimated considering gamma inter-arrival and general service time distributions. The performance is evaluated with different mobility and compared with that of guard channel scheme.